Proteinuria in pregnancy: Clinically driven considerations. Issue 1 (10th April 2018) - Cassia, Matthias Arnaldo; Daminelli, Giulia; Zambon, Marta; Cardellicchio, Manuela; Cetin, Irene; Gallieni, Maurizio
Introduction: Proteinuria assessment is a key test in pregnancy to evaluate renal and systemic well-being. The finding of proteinuria may allow diagnosis and ready intervention for pre-eclampsia and glomerulonephritis, which may compromise a favorable delivery. Moreover, pathological-range isolated proteinuria is a risk factor by itself for adverse outcomes during pregnancy. An appropriate interpretation of pathologic values of proteinuria is therefore of crucial importance. Patient presentation: We present the case of a 33-year-old apparently healthy woman at her first pregnancy who developed a clinically significant proteinuria during the first trimester; we describe the clinical workup and the management of the patient up to delivery. Conclusion: Urine analysis with dipstick or protein-to-creatinine ratio is part of the routine prenatal clinical care during pregnancy. Detection of a pathological proteinuria (>300 mg/24 h or equivalent) should never be underestimated, and timed urine collection is required, as well as a thorough medical examination. The main goal is to exclude pre-eclampsia, whereas the suspect of a primary kidney disease can be managed together with the nephrologist, both for management and treatment.